2022
DOI: 10.1186/s40538-022-00330-2
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of methomyl and crude extracts of Jatropha curcas against the terrestrial snail, Monacha obstructa (Gastropoda:Hygromiidae)

Abstract: Background The negative effect of over-reliance on the use of synthetic pesticides have led to the search for natural alternatives to pest control. This study was designed to evaluate the toxicity effect of the crude plant extracts of Jatropha (Jatropha curcas Linn.) seeds in comparison with methomyl on some histopathological changes of the terrestrial snail species Monacha obstructa (Pfeiffer, 1842). The toxicity effect of methomyl and crude extracts of ethanol and acetone extracts of Jatropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…On the other hand, the study results showed that a median-lethal concentration of Pcp caused histological alterations in the hepatopancreas and foot of the P. canaliculata. The results are similar to those reported by several authors; Ibrahim et al [42] reported that when treated with an LC 50 of methomyl, after 24 h, the foot of the snail Monacha obstructa showed a rupture of the epithelium covering the foot and the presence of a darkbrown pigment within the epithelial covering and connective tissue. The hepatopancreas exhibited breakdown of the digestive tubules as well as vacuolization, and the number of large granules increased.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the study results showed that a median-lethal concentration of Pcp caused histological alterations in the hepatopancreas and foot of the P. canaliculata. The results are similar to those reported by several authors; Ibrahim et al [42] reported that when treated with an LC 50 of methomyl, after 24 h, the foot of the snail Monacha obstructa showed a rupture of the epithelium covering the foot and the presence of a darkbrown pigment within the epithelial covering and connective tissue. The hepatopancreas exhibited breakdown of the digestive tubules as well as vacuolization, and the number of large granules increased.…”
Section: Discussionsupporting
confidence: 91%
“…It contains saponins, steroids, alkaloids, phenol, flavonoid, tannins, (Ruma & Sanchez, 2016). Jatropha contain secondary metabolites such salicylic acid, thymol, y-terpinene, potent cytotoxic, molluscicidal (Devappa et al, 2012;Ibrahim et al, 2022;Mahalakshmi et al, 2013;Muniz et al, 2020). These compounds can affect the metabolism of cold-blooded animals such as mollusks.…”
Section: Introductionmentioning
confidence: 99%
“…The histopathological changes in the gastropods of P. canaliculata were mainly characterized by epithelial cell degeneration and necrosis and a marked reduction in myofibers. The foot of Monacha obstructad ( Gastropoda : Hygromiidae ) snails treated with LC 50 of Jatropha showed rupture of the epithelium covering the foot, desquamation of the epithelium and presence of areas of connective tissue necrosis and destruction of the muscular tissue [ 57 ]. This is consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%